Basic Concepts of Ethics and the Teaching Profession - Lubis, Hasan Hamzah; Suhendri, Suhendri; Harahap, Muhammad Sapii (Edumaspul: Jurnal Pendidikan, 2024)
This research aims 1) to find out the meaning of ethics and the teaching profession, 2) to find out the basic principles or concepts of ethics and the teaching profession, and 3) to find out what the concept of ethics is in Islam. This research uses literature research (library research) or library research with a qualitative approach. The secondary data in this research is in the form of documents that support this research such as books, articles and journals. The results of this research are 1) ethics is a science that is related to efforts to determine whether actions carried out by humans are good or bad and a profession is essentially a statement or an open promise, that a person will devote himself to a position or job in the ordinary sense , because the person feels called to take up that job, 2) In professional ethics, teachers demand principles, namely responsibility, justice and autonomy, and 3) Ethics in Islam refers to two sources, namely the Koran and the Sunnah